Dominica : Request for Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; for Dominica. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2015)
This paper discusses Dominica's Request for Disbursement Under the Rapid Credit Facility (RCF). Tropical Storm Erika had a devastating effect on Dominica's economy. Total damage and loss is estimated at 96 percent of GDP. Real GDP is projected to decline by 3 percent in 2015, and reconstruction expenditures and the impact on agriculture and tourism activities are putting pressure on the fiscal and external accounts. Despite the high capital expenditures, the 2015 budget deficit will be contained to 2.4 percent of GDP reflecting strong grants, and the current account balance could deteriorate to a deficit of about 15 percent of GDP. The IMF staff supports the authorities' request for a disbursement under the RCF.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet